KERAMIK PORSELEN BERBASIS FELDSPAR SEBAGAI BAHAN ISOLATOR LISTRIK - Eva Indiani; Ngurah Ayu Ketut Umiati (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2009)
Electric solid insulator based on ceramics porcelain had been made by using local raw materials: 68% feldspar, 10% kaolinite and 22% quartz, and also added 0%, 5%, 10%, 15%, 20%, 25% cullet (From total mass). The forming process of the porcelain was conducted by milling the raw materials using ball mill and screened using 200 mesh screening. The samples were formed by using the dry-press method with the pressure of 50MPa, then the samples is sintered at temperature of 1000oC, 1050oC, 1100oC, 1150oC for 2 hours. The properties of the samples had been analyzed for their  shrinkage, density, bending strength and resistivity. The result of the experiment showed that the optimum value was reached by ceramic which was added by 15% cullet and sintered at temperature of 1100oC. This ceramic had shrinkage of 9,70%, density of 2,44 g/cm3, bending strength of 86,73 MPa and the resistivity at 25oC is 2,32x108 Ωcm